Cystic Echinococcosis in Pakistan: A Review of Reported Cases, Diagnosis, and Management - Khan, Aisha; Ahmed, Haroon; Khan, Huma; Saleem, Sadia; Simsek, Sami; Brunetti, Enrico; Budke, Christine M. (Elsevier, 2020)
Cystic echinococcosis (CE) is a zoonotic disease that occurs in humans and ungulates due to infection with the larval stage of the taeniid cestode Echinococcus granulosus sensu lato. It has been estimated that approximately one million people are infected annually, resulting in US$3 billion in human and livestock-associated direct and indirect losses per year. CE is a serious public health concern in many parts of the world, including Pakistan. This review discusses the causative agent as well as the epidemiology, diagnosis, and treatment of CE in Pakistan.
Keywords: Cystic echinococcosis; Prevalence; Human; Livestock; Diagnosis; Pakistan